SIKAP MODERAT DALAM NOVEL LINGKAR TANAH LINGKAR AIR KARYA AHMAD TOHARI - Farida Yufarlina Rosita; Yuentie Sova Puspidalia; Rangga Agnibaya; Sekar Putri Hapsari (Jurnal Semantik, 2024)
The author’s ideology is reflected in their work. One form of ideology is a moderate attitude which is reflected in the statements or sentences conveyed by the author through the characters in the story. This research is library research, with the research subject being the Lingkar Tanah Lingkar Air novels by Ahmad Tohari. The analysis was carried out by identifying the data by providing codes for the research problem and then analyzing it according to a moderate attitude. The results of the research show that there are 41 moderate attitudes in Lingkar Tanah Lingkar Air. Of the 41 attitudes, there are 7 attitudes of tolerance, 5 of national commitment, 3 of non-violence, 6 of public benefit, 2 of fairness, 2 of balance, 4 of obeying the constitution, and 12 of humanity. From the moderate attitude in the novel, it is hoped that readers can instill it in themselves so that they can act moderately in this multicultural society.